The difference in the significance of vocabulary and contextual expressions in translating the forty hadiths of Al-Nawawi in the english language - Asem Shehadeh Ali,; Mohamad Ahmad al-Qudah,; Mach Ly Ha Sa Nah, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This research aims to clarify the concept of significance and context, mention what is meant by translation, and clarify the effects of translating vocabulary or expressions in understanding the Prophetic hadiths and their differences. This research focuses on the impact of the difference in used vocabulary or contextual expressions on the significance between three books in translating the forty hadiths of al-Nawawi. And that there are different translations of a specific vocabulary that differ from one book to another, with a brief difference in meaning, and that the concept of the word in the source and the translated language in terms of terms or structure and other things is important in understanding the prophetic hadith and its purpose.